The Performance of Glycated Hemoglobin vs. Oral Glucose Tolerance Test in the Diagnosis of Glycemic Disorders among Women with Polycystic Ovary Syndrome in Southern Iraq - Mahmood Thamer Altemimi; Alaa Khattar Musa; Abbas Ali Mansour (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Obese women with polycystic ovary syndrome (PCOS) are at high risk for developing type 2 diabetes mellitus (T2DM). A baseline oral glucose tolerance test (2-h OGTT) is important to screen for dysglycemia in PCOS particularly those high risk women. Due to its advantages by fasting is not required and less day-to-day variability, glycated hemoglobin (HbA1c) might be a convenient screening tool. This study aimed to evaluate the performance of HbA1c vs. 2-h OGTT in the diagnosis of glycemic disorders in PCOS and to evaluate the correlation between glycemic disorders, insulin resistance (IR), and anthropometric measures.METHODS: One hundred and twenty nine women diagnosed with PCOS according to the Rotterdam 2003 criteria in Basrah were included in the study. All subjects were examined for weight, body mass index (BMI) and waist circumference (WC). Then they were tested for fasting glucose, 2-h OGTT, HbA1c, and fasting insulin to assess IR.RESULTS: The result of 2-h OGTT test showed that there were 21 subjects (16.1%) showed to have IGT. The result of HbA1c test showed that 25 subjects (19.4%) were diagonised with prediabetes. Meanwhile FPG test result showed that 34 subjects (26.4%) were having IFG. The HbA1c examination showed an underdetected the diagnosis of T2DM (0.8%) and an overdeteced diagnosis of prediabetes (19.4%) (p=0.021) and at HbA1c 5.55% (37.2 mmol/mol), the specificity was (74.3%) and sensitivity (56.5%) to discriminate normal from abnormal glucose status. Ninety nine women (76.7%) were either overweight or obese and most of them had IR (76.8%).CONCLUSION: Screening of glycemic disorders is crucial for PCOS by using 2-h OGTT regardless of risk factor and HbA1c seems to be an unsatisfactory screening tool to predict glycemic disorders in women with PCOS.KEYWORDS: PCOS, glycemic disorders, OGTT, HbA1c, insulin resistance, and prediabetes